Recent advancements in nanoparticle based drug delivery for gastrointestinal disorders. (4th March 2018) - Mittal, Rahul; Patel, Amit P.; Jhaveri, Vasanti M.; Kay, Sae-In S.; Debs, Luca H.; Parrish, James M.; Pan, Debbie R.; Nguyen, Desiree; Mittal, Jeenu; Jayant, Rahul Dev
ABSTRACT: Introduction : The emergent field of nanoparticles has presented a wealth of opportunities for improving the treatment of human diseases. Recent advances have allowed for promising developments in drug delivery, diagnostics, and therapeutics. Modified delivery systems allow improved drug delivery over traditional pH, microbe, or receptor dependent models, while antibody association allows for more advanced imaging modalities. Nanoparticles have potential clinical application in the field of gastroenterology as they offer several advantages compared to the conventional treatment systems including target drug delivery, enhanced treatment efficacy, and reduced side effects. Areas covered : The aim of this review article is to summarize the recent advancements in developing nanoparticle technologies to treat gastrointestinal diseases. We have covered the application of nanoparticles in various gastrointestinal disorders including inflammatory bowel disease and colorectal cancer. We also have discussed how the gut microbiota affects the nanoparticle based drug delivery in the gastrointestinal tract. Expert opinion : Nanoparticles based drug delivery offers a great platform for targeted drug delivery for gastrointestinal disorders. However, it is influenced by the presence of microbiota, drug interaction with nanoparticles, and cytotoxicity of nanoparticles. With the advancements in nanoparticle technology, it may be possible to overcome these barriers leading to efficient drug delivery for gastrointestinal disorders based on nanoparticle platform.